Beyond conventional boundaries uncertainty in research and practice with children - Bishop, Russell; SpringerLink (Online service). (Rotterdam Sense Publishers, 2011)
The impact which my decisions will have on this child's life is enormous and far-reaching. Relatively speaking, the impact which she will have on my life is minimal. She will be a thought in my mind, at most, an incessant worry. Yet even this is grudged we professionals tell each other that we have to leave our work behind when we go home, don't take your work worries with you... (p.85). This book calls for a re-thinking of practice and research with children in the helping professions. In the context of today's fast world with its requirement for order and precision, the practice of working with children is imbued with ethical dilemmas which practitioners may or may not be aware of. It is important for the practitioner to feel suspended in uncertainty before taking action. In terms of research, the complexity of what is explored is reflected in the complexity of the research method. In a parallel writing, this uncertainty is a central theme in practice through the narrative of three stories of the author's involvement with children referred for support. The book explores how uncertainty and anxiety can be turned to good use rather than being a debilitating force to the practising psychologist. It also touches upon issues o performativity, accountability and efficiency in the becoming of professionals in the helping professions.
Electronic reproduction.
Keywords: Children -- Research; Children -- Research -- Methodology; Electronic books